The SEM & AFM images of MEH-PPV films below CLA region - Nurjuliana, Juhari; Wan Haliza, Abd Majid, Prof. Dr.; A. I., Zainol (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.